Primitive peripheral neuroectodermal tumor of the kidney, case report. - Bustamante Chávez , Rubí X. (2023)
Introduction: Peripheral primitive neuroectodermal tumor of the kidney (PNETk) is a very aggressive rare disease that mainly affects young men. Case report: A 19-year-old male patient with symptoms of abdominal pain, hematuria and a palpable mass, the tomography shows a large left renal tumor. Conventional radical nephrectomy was performed and sent for pathology study plus histochemistry, resulting in PNETk. The patient then continued his oncology management for chemotherapy initially. Conclusion: The PNETk that we describe represents the first case reported in our country, it constitutes a unique clinical entity due to its rarity, being a challenge to make a diagnosis and its behavior and management is still based on case reports due to its infrequency.